HDAC2-dependent remodeling of KCa2.2 (KCNN2) and KCa2.3 (KCNN3) K+ channels in atrial fibrillation with concomitant heart failure - Rahm, Ann-Kathrin; Wieder, Teresa; Gramlich, Dominik; Müller, Mara Elena; Wunsch, Maximilian N.; El Tahry, Fadwa A.; Heimberger, Tanja; Weis, Tanja; Most, Patrick; Katus, Hugo; Thomas, Dierk; Lugenbiel, Patrick (Life sciences, 2021)
Aims - Atrial fibrillation (AF) with concomitant heart failure (HF) is associated with prolonged atrial refractoriness. Small-conductance, calcium-activated K+ (KCa, KCNN) channels promote action potential (AP) repolarization. KCNN2 and KCNN3 variants are associated with AF risk. In addition, histone deacetylase (HDAC)-related epigenetic mechanisms have been implicated in AP regulation. We hypothesized that HDAC2-dependent remodeling of KCNN2 and KCNN3 expression contributes to atrial arrhythmogenesis in AF complicated by HF. The objectives were to assess HDAC2 and KCNN2/3 transcript levels in AF/HF patients and in a pig model, and to investigate cellular epigenetic effects of HDAC2 inactivation on KCNN expression. - Materials and methods - HDAC2 and KCNN2/3 transcript levels were quantified in patients with AF and HF, and in a porcine model of atrial tachypacing-induced AF and reduced left ventricular function. Tachypacing and anti-Hdac2 siRNA treatment were employed in HL-1 atrial myocytes to study effects on KCNN2/3 mRNA and KCa protein abundance. - Key findings - Atrial KCNN2 and KCNN3 expression was reduced in AF/HF patients and in a corresponding pig model. HDAC2 displayed significant downregulation in humans and a tendency towards reduced expression in right atrial tissue of pigs. Tachypacing recapitulated downregulation of Kcnn2/KCa2.2, Kcnn3/KCa2.3 and Hdac2/HDAC2, indicating that high atrial rates trigger epigenetic remodeling mechanisms. Finally, knock-down of Hdac2 in vitro reduced Kcnn3/KCa2.3 expression. - Significance - KCNN2/3 and HDAC2 expression is suppressed in AF complicated by HF. Hdac2 directly regulates Kcnn3 mRNA levels in atrial cells. The mechanistic and therapeutic significance of epigenetic electrophysiological effects in AF requires further validation.
Im Titel ist Ca jeweils tiefgestellt, "+" ist hochgestellt
Available online 10 December 2020
Gesehen am 23.03.2021